Evaluation of working memory in relation to cochlear implant consonant speech discrimination - Mai M. El Ghazaly; Mona I. Mourad; Nesrine H. Hamouda; Mohamed A. Talaat (The Egyptian Journal of Otolaryngology, 2021)
Abstract Background Speech perception in cochlear implants (CI) is affected by frequency resolution, exposure time, and working memory. Frequency discrimination is especially difficult in CI. Working memory is important for speech and language development and is expected to contribute to the vast variability in CI speech reception and expression outcome. The aim of this study is to evaluate CI patients’ consonants discrimination that varies in voicing, manner, and place of articulation imparting differences in pitch, time, and intensity, and also to evaluate working memory status and its possible effect on consonant discrimination. Results Fifty-five CI patients were included in this study. Their aided thresholds were less than 40 dBHL. Consonant speech discrimination was assessed using Arabic consonant discrimination words. Working memory was assessed using Test of Memory and Learning-2 (TOMAL-2). Subjects were divided according to the onset of hearing loss into prelingual children and postlingual adults and teenagers. Consonant classes studied were fricatives, stops, nasals, and laterals. Performance on the high frequency CVC words was 64.23% ± 17.41 for prelinguals and 61.70% ± 14.47 for postlinguals. These scores were significantly lower than scores on phonetically balanced word list (PBWL) of 79.94% ± 12.69 for prelinguals and 80.80% ± 11.36 for postlinguals. The lowest scores were for the fricatives. Working memory scores were strongly and positively correlated with speech discrimination scores. Conclusions Consonant discrimination using high frequency weighted words can provide a realistic tool for assessment of CI speech perception. Working memory skills showed a strong positive relationship with speech discrimination abilities in CI.